Multiple alignment of genomic sequences using CHAOS, DIALIGN and ABC - Pöhler, Dirk (Oxford University Press, 2005)
Comparative analysis of genomic sequences is a powerful approach to discover functional sites in these sequences. Herein, we present a WWW-based software system for multiple alignment of genomic sequences. We use the local alignment tool CHAOS to rapidly identify chains of pairwise similarities. These similarities are used as anchor points to speed up the DIALIGN multiple-alignment program. Finally, the visualization tool ABC is used for interactive graphical representation of the resulting multiple alignments. Our software is available at Göttingen Bioinformatics Compute Server (GOBICS) at